REFORMASI PARTAI POLITIK DALAM SISTEM KETATANEGARAAN INDONESIA: ANALISIS NORMATIF DAN KELEMBAGAAN - Sakinah, Siti; Nur, Insan Tajali; Hamzah, Herdiansyah (Jurnal Ilmiah Advokasi, 2025)
Political parties play a vital role in Indonesia’s constitutional system, particularly in fulfilling democratic functions such as political participation, leadership recruitment, and policy formulation and oversight. However, in the post-reform era, political parties continue to face persistent internal and external challenges that weaken their strategic role in sustaining democratic governance. This study employs a normative-juridical and comparative approach, drawing upon statutory analysis, scholarly literature, and institutional practices of political parties in Indonesia and selected democratic countries. The findings reveal that the stagnation of political party reform is primarily driven by the weakness of political education, the lack of internal democracy, and limited financial transparency. The study concludes that amending Law No. 2 of 2011 on Political Parties is essential to strengthen institutional integrity and public accountability. Its main scholarly contribution lies in proposing a conceptual model of “three pillars of party reform”—political education, internal democratization, and financial transparency—which can serve as a normative framework for designing a more adaptive, inclusive, and civilized party system within Indonesia’s democracy.Keywords: Democratization; Political Parties; Reform, Transparency